1965
DOI: 10.5070/c58f32d49q
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Protection Studies with Strains of Concave Gum and Psorosis Viruses

Abstract: Cross-Protection Studies with Strains o f Concave G u m and Psorosis Virusesphenomena in sweet orange seedlings infected with various California strains of psorosis virus, including concave gum, were first reported by Wallace ( 16, 17), who pointed out that in some instances protection was only partial. The cross-protection or virusstrain-interference reaction has sometimes been useful in diagnosing psorosis in cases where leaves of sweet orange seedlings failed to show definitive symptoms.I n 1960 an indexing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…PsA protects against a challenge from the more severe bark lesions induced by the more aggressive psorosis (PsB) (Wallace, 1957). Citrus psorosis disease is worldwide in many parts of the world, including South America and the Mediterranean areas (Roistacher, 1993). In Egypt, some investigators isolated and identified CPsV (Nour-Eldin, 1956;Nour-Eldin, 1957;Fahmy et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PsA protects against a challenge from the more severe bark lesions induced by the more aggressive psorosis (PsB) (Wallace, 1957). Citrus psorosis disease is worldwide in many parts of the world, including South America and the Mediterranean areas (Roistacher, 1993). In Egypt, some investigators isolated and identified CPsV (Nour-Eldin, 1956;Nour-Eldin, 1957;Fahmy et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, RT-PCR, the alternative detection method was applied by using several primers (Martin et al, 2004). Biological indexing could be performed for CPsV detection by graft-inoculating citrus in sensitive indicator plants such as sweet orange and then testing for cross-protection with severe isolate (PsB) (Roistacher and Calavan, 1965;Roistacher, 1993). A new method of biological indexing was organized for diagnosis of Citrus viruses and viroids by using indicator cutting as an alternative to seedlings (ElBacki et al, 2005;El Sayed, 2005;D'nghia et al, 2009).…”
Section: Introductionmentioning
confidence: 99%